2010
DOI: 10.1007/978-1-4419-7913-1_5
|View full text |Cite
|
Sign up to set email alerts
|

The Latrophilins, “Split-Personality” Receptors

Abstract: Latrophilin, a neuronal "adhesion-G protein-coupled receptor", is the major brain receptor for alpha-latrotoxin, a black widow spidertoxin which stimulates strong neuronal exocytosis in vertebrates. Latrophilin has an unusual structure consisting of two fragments that are produced by the proteolytic cleavage of the parental molecule and that behave independently in the plasma membrane. On binding an agonist, the fragments reassociate and send an intracellular signal. This signal, transduced by a heterotrimeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 76 publications
(175 reference statements)
1
46
0
Order By: Relevance
“…In contrast to these results, the structure of GAIN domain suggests that the site of cleavage is buried within a rigid domain structure, and the resulting subunits cannot be easily detached or recombined unless the protein is substantially denatured (84). This also accounts for the high structural similarity between GAIN domains of noncleavable and cleavable AdhesionGPCRs (38).…”
Section: Adhesion-gpcrs-receptors With Split Personality?mentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast to these results, the structure of GAIN domain suggests that the site of cleavage is buried within a rigid domain structure, and the resulting subunits cannot be easily detached or recombined unless the protein is substantially denatured (84). This also accounts for the high structural similarity between GAIN domains of noncleavable and cleavable AdhesionGPCRs (38).…”
Section: Adhesion-gpcrs-receptors With Split Personality?mentioning
confidence: 81%
“…Phosphorylation of Adhesion-GPCRs that couple to G proteins such as latrophilin 1 and GPR56 is demonstrated (60,84,130,134). The CTF of latrophilin 1 is phosphorylated in rat brain but not in cultured cells, suggesting that phosphorylation occurs in vivo, perhaps as a result of physiological brain function that cannot be recapitulated in vitro (84).…”
Section: Phosphorylation Of the Ctfmentioning
confidence: 99%
“…However, this region is contained in the Stalk domain needed to bind its ligand, -latrotoxin (Krasnoperov et al 1999;Silva & Ushkaryov 2010). The in silico analysis suggested a role of this region as ESEs, which are discrete sequences within exons that promote both constitutive and alternative splicing.…”
Section: Discussionmentioning
confidence: 99%
“…Latrophilin receptors, a neuronal adhesion G-protein-coupled receptor, was the other class B GPCR identified in the study. Previous studies in nematodes have shown that it controls neurotransmitter release on binding with specific ligands in adult brains (Silva et al, 2010). Indepth study of latrophilin-related GPCR signaling pathway in An.…”
Section: Enrichment Of Gpcrs In the Brain Studymentioning
confidence: 99%